Boletellus putuoensis (Boletaceae, Boletales), a new bolete from subtropical China - Xu, Chang; Zhang, Xu; Chen, Yun-Xia; Xue, Rou; Le, Zhi-Fang; Wang, Jian-Rui; Li, Yi; Zeng, Nian-Kai (Phytotaxa, 2022)
Boletellus putuoensis (Boletaceae, Boletales) from Zhejiang Province, a subtropical region of eastern China, is described as a new species based on morphological and phylogenetic evidence. A detailed description, color photos of fresh basidiomes, and line-drawings of microstructures of the new species are presented as well as comparisons with related species.